ECONOMICS CAPITALISM, THE BIRTH OF STATE AND ALQURAN RULES - chairul ihsan burhanuddin (AkMen JURNAL ILMIAH, 2020)
The long-standing socialist capitalist economy is a paradigm in economic activity as if it backfires within the paradigm itself. Looking at increasingly uncertain economic conditions, make people think to find solutions to the problems that occur. The Mahzab thought of Karl Marx and Adam Smith was not as beautiful as imagined. Monopolistic concept is precisely raises human welfare issues and natural imbalance that can no longer be tolerated. This concept of thought has finally reached the saturation point. Islamic economics or Sharia economics had become an alternative in addressing the problem. However, is the sharia economy in accordance with the provisions established by Allah SWT in the Qur'an? Returning to the sharia rule, does not mean to return to the rules established by Allah SWT. The research method is done through a qualitative approach, using the Library Research method. The results of this study provide an economic perspective by providing explanations based on the verses contained in the Qur'an. Starting from solutions in the problems of production and consumption processes, trading, the concept of balance, and debt management of receivables.